Neurobiological and therapeutic landmarks of depression associated with Alzheimer’s disease dementia - Ilinca Untu; Michael Davidson; Gabriela-Dumitrita Stanciu; Jonathan Rabinowitz; Jonathan Rabinowitz; Romeo-Petru Dobrin; Diana-Sabina Vieru; Bogdan-Ionel Tamba; Bogdan-Ionel Tamba (Frontiers in Aging Neuroscience)
Depression in Alzheimer’s disease (AD) dementia has become an increasingly recognized public health concern due to its high prevalence and substantial impact on patient outcomes. Despite extensive research having been conducted over the past decades, the precise causal mechanisms and the nature of the relationship between depression and AD dementia remain incompletely understood. This narrative review examines the bidirectional interaction between depression and Alzheimer’s disease, emphasizing shared neurobiological pathways, including neurotransmitter dysregulation, neuroinflammation, abnormalities in the hypothalamic–pituitary–adrenal (HPA) axis, and deficits in neuroplasticity. These mechanisms likely contribute to the acceleration of neurodegeneration in AD and the onset or worsening of depressive symptoms. Current therapeutic approaches remain largely nonspecific, with a lack of targeted therapies that address the unique pathophysiological context of depression in AD. While progress has been made, key research gaps remain, particularly in understanding the complex biological interactions between these two conditions. Future research should focus on identifying specific biomarkers and developing personalized treatment strategies tailored to the neurobiological features of both depression and AD. By addressing these neurobiological mechanisms, we can develop more effective and targeted interventions, ultimately improving patient outcomes and advancing clinical care for this dual pathology.